Prevalence and related risk factors of tobacco, alcohol and illicit substance use among university students - (:unkn) unknown (EUROPEAN JOURNAL OF PSYCHIATRY, 2013)
Background and Objectives: The objective of this study was to determine the frequency of cigarette, alcohol and substance use and the possible associations between different types of substance use and various risk factors among university students. Methods: A self-assessment questionnaire was administered to 4762 students from Canakkale Onsekiz Mart University. The risk factors associated with cigarette, alcohol and substance use were investigated with logistic regression analysis. Results: The frequencies of regular or occasional tobacco and alcohol use were 38.6% and 46.3% respectively. The frequency of using substance at least once in life time was 6.3% among students. In the present study, male gender was found to be a statistically significant risk factor associated with all of the three dependent variables. The statistically significant risk factors for using alcohol were studying in college and vocational schools, having a parent with high school and above educational level, having a family income of 1226 USD's and above, having tried tobacco once or a couple of times and using tobacco occasionally or regularly, and having used another substance at least once. Substance use risk was found to be higher in those with higher depression scores, in those who tried tobacco once or a couple of times and who were not using regularly, and who were using tobacco or alcohol occasionally or regularly. Conclusions: The practices and activities of the health center incorporated in the university should be enhanced for the establishment of effective control programs related to tobacco, regular alcohol and substance use.
Keywords: Cigarette; Alcohol; Illicit substance; University student; PATTERNS; SMOKING; SAMPLE